Monitoring Early Age Strength and Hardening of Concrete Using Ultrasonic Guided Waves - Randhawa, Jashanjeet (My University, 2011)
At early ages of concrete structures, strength monitoring is important to determine the structure’s readiness for service. Concrete setting and hardening process are the most critical phases during construction works, influencing to properties of concrete structure, so the application of efficiency non-destructive test methods for early age concrete properties determination is crucial. In this study, apart from standardized methods like Pull out and Vicat needle methods to study the setting of concrete, ultrasonic pulse velocity and suitability of ultrasonic guided waves methods for young concrete characterization is also explored. In ultrasonic method, guided wave is transmitted and received through a waveguide that is embedded in early age concrete. As the cementitious material sets and hardens, the strength of the received waves changes, indicating the transition from semi-fluid to solid state. This thesis proposes through transmission system; a wave transmitted on one end of an embedded waveguide using a sensor arrangement and then it is received on the opposite end of the propagating bar with another sensor. This approach monitors the attenuation of the fundamental guided (Longitudinal) wave mode, resulting from the leakage of energy from the cylindrical steel rod to the surrounding cementitious material. The evolution of the material’s properties is related to the energy leakage or attenuation of the guided wave. Experiments were performed on concrete mixtures with varying slumps like 35mm (Low), 80mm (Moderate) & 350mm (High). For ultrasonic guided waves, beam specimens of size 150 mm x150 mm x 300 mm with embedded mild steel rod of 25mm diameter and 600 mm length were used to monitor early strength (i.e. first 24 hrs of hydration) & hardening process (i.e. during curing). Ultrasonic pulse velocity was also carried out side by side on a standard cube (150 mm x 150 mm x 150 mm) of same concrete mixture to study the microstructure development of concrete.
M.E. (Structures)
Keywords: Concrete; Ultrasonic Guided Waves